Performance of Bali Cattle on Substitution Feeding Fermented Straw - M. Musdalifa; Bahri Syamsuryadi; Abdul Hakim Fattah (UNIVERSITAS SEMBILANBELAS NOVEMBER KOLAKA, 2018)
The purpose of this research is to know the increase of body weight, feed consumption, feed efficiency and conversion of Bali cattle feed given fermented straw as substitution of Elephant Grass. The method used in this Experimental study Method with Randomized Block Design with four treatments and three replications. P2: Elephant Grass 100% (control) P1: Elephant Grass 75% + 25% fermented straw, P2 treatment: Elephant Grass 50% + 50% fermentation straw and P3 Treatment: 25% Grass + Finger straw 75 %. The observed changes were weight gain (kg/day), feed consumption (kg/day), feed efficiency and feed conversion in Bali cattle. The data obtained were analyzed in various ways with Duncan. The result of this research showed that by giving substitution of fermented straw to determine the performance of bovine cow have a real effect (P ≤.05) to the value of body weight gain, feed consumption, feed conversion and efficiency of feed. It shows that with the difference of feeding substitution of fermented straw can give the real effect on the increase of body weight of Bali cattle with feeding of forage grass 50% elephant + 50% fermented straw.